1998
DOI: 10.1111/0162-895x.00128
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarianism and Economic Threat: Implications for Political Behavior

Abstract: This study examined whether authoritarians experiencing economic threat are more likely than other authoritarians to support social policy and political agendas that restrict benefits or curtail rights for disadvantaged groups. A sample of 131 college students completed questionnaires that measured authoritarianism, degree of economic and societal insecurity, and attitudes toward eight political issues. Economic and social insecurity were indexed to perceptions of whether one's standard of living had declined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
74
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 18 publications
5
74
0
2
Order By: Relevance
“…Confirming our HP1.3, and consistent with Duckitt (1992), Feldman and Stenner (1997), Rickert (1998) and Stevens, Bishin, and Barr (2006), perceived societal threat to safety exerted a significant, positive influence on RWA, whereas perceived personal threat to safety did not influence it. Based on Feldman and Stenner's (1997) interpretation, this result should be considered as consistent with Duckitt's (1989) concept of authoritarianism as a group-related phenomenon, leading to the prediction that threats to group integrity, status, cohesion and/or identity, rather than to personal well-being, tend to activate authoritarianism.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Confirming our HP1.3, and consistent with Duckitt (1992), Feldman and Stenner (1997), Rickert (1998) and Stevens, Bishin, and Barr (2006), perceived societal threat to safety exerted a significant, positive influence on RWA, whereas perceived personal threat to safety did not influence it. Based on Feldman and Stenner's (1997) interpretation, this result should be considered as consistent with Duckitt's (1989) concept of authoritarianism as a group-related phenomenon, leading to the prediction that threats to group integrity, status, cohesion and/or identity, rather than to personal well-being, tend to activate authoritarianism.…”
supporting
confidence: 87%
“…Nonetheless, Rickert (1998) and Stevens, Bishin, and Barr (2006), who directly assessed authoritarianism, substantially confirmed Feldman and Stenner's results.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…There is by now substantial archival research suggesting that during times of societal crisis, people are more likely to turn to authoritarian leaders and institutions for security, stability, and structure (e.g., Doty, Peterson, & Winter, 1991;McCann, 1997;Peterson et al, 1993;Rickert, 1998;Sales, 1972Sales, , 1973. Sales (1972), for instance, found that during periods of severe economic threat (the depression years of 1930 -1939), people were more likely to join authoritarian churches, such as Southern Baptist and Seventh Day Adventist, and less likely to join nonauthoritarian churches, such as Northern Baptist and Episcopalian, compared with periods of relative prosperity (1920 -1930).…”
mentioning
confidence: 99%